PENENTUAN CADANGAN PREMI ASURANSI DWIGUNA MENGGUNAKAN METODE ILLINOIS BERDASARKAN HUKUM MORTALITAS WEIBULL - DEVI, AYU EKA FANNY; WIDANA, I NYOMAN; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 10 No 4 (2021)DO - 10.24843/MTK.2021.v10.i04.p347, 2021)
Endowment insurance provides protection benefit and saving benefits. In the endowment insurance the insured party (insurance participant) must be paid the premiums. In addition to premiums, there is also policy value, which is sum of money that must be collected by the company in preparation for claim payment. The purpose of this study was to determine calculation of policy value in endowment insurance using Illinois method based on Weibull Mortality Law. In this study used secondary data from United States Life Table in the form of mortality probability data. Calculation value using Weibull mortality law, then the policy value calculated by Illinois method. The result of this study is policy value using Illinois Method based on Weibull Mortality Law is bigger than policy value using Illinois method without Weibull mortality law in the first year until year 20th. After year 20th, the policy value using Illinois method based on Weibull mortality law is smaller than policy value using Illinois method without Weibull mortality law, while at the end of the insurance year which is year 30th, the policy value with or without Weibull mortality law generates the same value.